Adjectives and proper nouns in Romance and English - Giurgea, Ion (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2007)
My contribution examines some problems raised by adjectival restrictive modification of proper nouns. I begin with a contrast between the way in which this modification is achieved in English and in Romance, particularly in Romanian: while English uses the same structure for proper and common nouns, in Romance, in the case of the definite article, other structures are preferred (and in Romanian obligatory), which have the form PN+Art+Adj (structures which I call "identificatory appositions"). After briefly examining the types of conversion of PNs to CNs and the behaviour of determiners with PNs, I discuss some possible solutions to the contrast between Romance and English, and conclude that Romance uses the identificatory apposition for a special type of restrictive modification of PNs, one in which a selection among familiar entities is involved. In Romanian instead of preference we find obligatoriness for morphological reasons. Then I sketch an analysis of the structure of identificatory apposition, associating it to a special semantic rule from which we can derive most of its properties. In the end I present some further applications of the structure I have proposed.